DAMPAK PROGRAM AKREDITASI TERHADAP PENINGKATAN STANDAR MUTU PENDIDIKAN DI SEKOLAH DASAR DI DAERAH TERPENCIL - Indah Puspitasari; Siti Aimah (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
This study uses a qualitative approach with a case study method, namely collecting data through in-depth interviews, observations, and documentation. The results show that accreditation contributes significantly to improving the quality of education by encouraging increased teacher competence, better school management, and improved facilities. The school experienced an increase in student learning motivation, where 75% of students reported being more motivated after accreditation. In addition, 70% of parents stated that good educational facilities contributed greatly to children's interest in learning. This study provides a new perspective on the effectiveness of accreditation in remote schools that face unique challenges compared to urban areas. Despite constraints in infrastructure and resources, the accreditation program has been shown to improve educational standards. The conclusion of this study confirms that the accreditation program is not only important to meet national education standards, but also plays a role in creating a more conducive learning environment, improving the quality of education, and increasing public awareness of the importance of quality education in remote areas.